2019
DOI: 10.5114/amsad.2019.86749
|View full text |Cite
|
Sign up to set email alerts
|

Stroke and breast cancer in the United States during 2007–2017

Abstract: Introduction The main purpose of this work is to study the malignant neoplasms of the breast and the incidence of strokes in the United States and to find not only statistically significant predictors for cancer, but also a possible association between breast cancer and stroke. Material and methods The statistical methods used to derive the results of this work are χ 2 and one-way analysis of variance (ANOVA) tests, in order to check the stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Some cases series and retrospective study has showed that breast cancer is a risk factor for stroke. [ 14 ] Nilsson et al performed an observational study, and, from comparing breast cancer patients with stroke to patients without, drew the conclusion that the risk of stroke was increased in patients with breast cancer [RR = 1.12 95% CI = (1.07, 1.17)]. It seemed that breast cancer was a risk factor for stroke, especially ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Some cases series and retrospective study has showed that breast cancer is a risk factor for stroke. [ 14 ] Nilsson et al performed an observational study, and, from comparing breast cancer patients with stroke to patients without, drew the conclusion that the risk of stroke was increased in patients with breast cancer [RR = 1.12 95% CI = (1.07, 1.17)]. It seemed that breast cancer was a risk factor for stroke, especially ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…The literature includes studies regarding the development of stroke in various disease settings such as prostate [16] and breast cancer [17]. However, as a cardiac disorder, estimation of development of ischaemic stroke is especially clinically important for patients with PFO, where PFO closure, although still controversial, is an option that may preclude worse outcome [5,18].…”
Section: Discussionmentioning
confidence: 99%
“…The high rate of BC in highly developed countries is attributed to the higher prevalence of risk factors, such as late motherhood, nulliparity, non-breastfeeding or short-term breastfeeding, early age menarche, menopause at older ages, use of oral contraceptives and hormone replacement, alcohol intake, overweight, diet rich in processed foods and red meats, physical inactivity, work shifts, unemployment having worked before, exposure to ionizing radiation such as mammography and radiotherapy and to endocrine disrupting chemicals 3 8 .…”
Section: Introductionmentioning
confidence: 99%